2011
DOI: 10.1182/blood-2010-11-316893
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulation of fetal to adult hemoglobin switching: new therapeutic opportunities

Abstract: In humans, embryonic, fetal, and adult hemoglobins are sequentially expressed in developing erythroblasts during ontogeny. For the past 40 years, this process has been the subject of intensive study because of its value to enlighten the biology of developmental gene regulation and because fetal hemoglobin can significantly ameliorate the clinical manifestations of both sickle cell disease and ␤-thalassemia. Understanding the normal process of loss of fetal globin expression and activation of adult globin expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
114
1
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 159 publications
(122 citation statements)
references
References 98 publications
1
114
1
6
Order By: Relevance
“…Our study, together with recent publications, demonstrate that its binding domain, located 5' to the dgene, is a major player in the complex network of factors involved in HbF expression. We found that the loss of this region is associated with an increase of 2.7 g/dL of HbF, which would be sufficient to compensate the Hb lack in bthal major patients 13 and would be sufficient to prevent sickle cell anemia complications. These findings would help to focus efforts towards defining new therapeutic strategies through BCL11A silencing or preventing its binding for HbF reactivation.…”
Section: Resultsmentioning
confidence: 89%
“…Our study, together with recent publications, demonstrate that its binding domain, located 5' to the dgene, is a major player in the complex network of factors involved in HbF expression. We found that the loss of this region is associated with an increase of 2.7 g/dL of HbF, which would be sufficient to compensate the Hb lack in bthal major patients 13 and would be sufficient to prevent sickle cell anemia complications. These findings would help to focus efforts towards defining new therapeutic strategies through BCL11A silencing or preventing its binding for HbF reactivation.…”
Section: Resultsmentioning
confidence: 89%
“…90,91 Efforts in this area were advanced with the discovery that BCL11A is a major regulator of developmentally stage-specific repression of the g-globin gene. 92 Genetic deletion of BCL11A has been used to correct sickle cell disease in adult mice by interference with fetal hemoglobin silencing.…”
Section: Hemoglobin Disordersmentioning
confidence: 99%
“…[9][10][11] The silencing of HbF in adults is also mediated by epigenetic changes, including DNA methylation and histone modifications, and several chromatin-modifying enzymes, including DNA methyltransferases, 12 HDACs, 8 PRMT5, 13 and LSD1, 12,14 have been shown to contribute to this process. However, it is likely that other epigenetic regulators remain to be identified.…”
Section: Introductionmentioning
confidence: 99%